The Influence of Word of Mouth and Service on Tourist Interest in Visiting Ujong Seuke Beach in Bireuen Regency - Liza April Nabila; Denny Firmansyah (Journal of Innovative and Creativity, 2026)
The analysis of the influence of Word of Mouth and service quality on tourist interest in visiting Ujong Seuke Beach, Bireuen Regency, has important relevance in the development of regional tourism destinations. Increased interest in visiting is not only determined by the physical attractiveness of the destination, but also by information disseminated among tourists and the quality of service directly experienced. Word of Mouth acts as a source of information that is considered more credible because it comes from real experiences, while service quality reflects the interaction of tourists with the management and available facilities. A quantitative approach with a survey method was used to measure the relationship between variables numerically by distributing questionnaires to 100 respondents. The data obtained were analyzed using multiple linear regression to test the partial and simultaneous effects of the variables studied. The results of the analysis indicate that Word of Mouth has a positive and significant effect on tourist interest in visiting, evidenced by the calculated t-value of 2.956 which is greater than the t-table of 1.984 and a significance value of 0.004. Service quality also has a positive and significant effect with a more dominant influence, indicated by the calculated t-value of 9.580 which exceeds the t-table of 1.984 and a significance value of 0.000. Simultaneously, Word of Mouth and service quality explain 56.6% of the variation in tourist visit interest, while the remaining 43.4% is influenced by other factors outside the model. This finding confirms that strengthening communication between tourists and improving service quality are key strategies in increasing visit interest in coastal tourist destinations